PELATIHAN PENYUSUNAN ASESMEN ALTERNATIF DALAM KURIKULUM MERDEKA BAGI GURU SMA/SMK/MA DI KECAMATAN LEIHITU MALUKU TENGAH - Tamaela, Elsina S; Latununuwe, Altje; Huliselan, Estevanus K; Nirahua, Juliana; Limba, Anatasija; Latupeirissa, Asry N; Barus, Carolina S A; Singerin, Sarlota; Sapulete, Heppy; Malawau, Seska; Lesiela, Yulia; Mahu, Sri Jumiati (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Assessment plays an essential role in decision-making related to student success, especially in the Independent Curriculum, which encourages a holistic assessment approach. This Community Service Program (PKM) aims to improve the skills of SMA/SMK/MA teachers in Leihitu District in compiling alternative assessments that are able to evaluate various aspects of student competency. This PKM was carried out for two days with training and mentoring methods. The activities were divided into two parts, namely two-day training and the second part was mentoring in compiling assessments. The results of this training showed an increase in teachers' ability to compile alternative assessments from the sufficient category to the good category. This finding confirms that the PKM activity has succeeded in improving teachers' ability to compile alternative assessments in the implementation of the Independent Curriculum. These results show the importance of ongoing training for teachers to support the implementation of more effective assessments in accordance with the Independent Curriculum, which ultimately strengthens the quality of decisions related to student learning development.